Slow magnetization dynamics in Co(ii)/Co(iii) triethanolamine/pivalate complexes. Issue 47 (21st November 2018) - Sarto, Carolina; Rouzières, Mathieu; Liu, Jun-Liang; Bamberger, Heiko; van Slageren, Joris; Clérac, Rodolphe; Alborés, Pablo
Abstract : We report a combined computational and experimental study of SMM properties of two new pivalate cobalt complexes. Abstract : We report the synthesis, structural characterization and a combined computational and experimental study of the magnetic properties of two pivalate cobalt complexes, a mononuclear Co(ii ) one and a tetranuclear Co(ii )3 Co(iii ) mixed valence polynuclear one. The latter shows SMM behaviour revealed under an applied DC field with a thermal barrier of ca . 30 cm −1 competing with direct and Raman relaxation processes. The Orbach thermal barrier can be understood from the doublets energy ladder arising from the anisotropic exchange interaction among ground S eff = 1/2 of each Co(ii ) sites. The strong local zero-field splitting of the S = 3/2 Co(ii ) states affords these well isolated ground Kramers doublets. DC and AC magnetic susceptibility measurements as well as HF-EPR spectra support this interpretation. CASSCF quantum chemical computations have been also performed in order to aid the overall comprehension of the magnetic behaviour in the reported complexes.